دراسة البنية الإلكترونية لبلورة Bi12SiO20بوساطة الانعكاس الضوئي* - دالاتي برهان; صارم عمار (Latakia University Journal -Basic Sciences Series, 2018)
تم قياس معامل طيف انعكاس البلورة الأحادية Bi12SiO20 في مجال الطاقة (1,5-12 eV) في درجة حرارة الغرفة لوحظ في طيف الانعكاس بنية غنية مطابقة للانتقالات الإلكترونية بين العصابات. تم تفسير البنية الضوئية الملاحظة في طيف الانعكاس بدلالة الانتقالات ما بين السويات O2-(2p) وعدد من عصابات الناقلية. حدد مخطط عصابات الطاقة بشكل رئيسي بوساطة بنية الشبكة بزموث-أكسجين. وقد تبين أن الانتقالات الضوئية تحدث عند النقاط السرجية (Saddle points) على المستقيم G-P(L). وإن احتمال الانتقالات الضوئية عند النقطتينP و H ضعيف بسبب انخفاض كثافة الاحتمالات المتوقع هناك. The normal-incidence reflectance spectrum of Bi12SiO20 single crystal in the energy range from 1.5 to 12 eV at room temperature has been measured. A rich structure corresponding to the optical interband transitions were observed in the reflectivity spectrum. The observed optical structures in the spectrum were interpreted in terms of transitions between O2-(2p) levels and the various conduction bands. The energy band scheme of Bi12SiO20 is determined mainly by the bismuth and oxygen net structure. The optical transitions occur at the saddle points on the G-P(L) line. The probability of transitions at the P and H points is low, because of the density of states is expected to be low there.